Soft Probe Scanning Electrochemical Microscopy with Spider Array for Visualizing Biomarkers and Redox Active Proteins in Animal Tissues. (19th April 2017) - Lin, Tzu-En; Lu, Yu-Jen; Sun, Chia-Liang; Chen, Jyh-Ping; Lesch, Andreas; Girault, Hubert H
Abstract : We present soft spider array for gentle contact mode scanning electrochemical microscopy (SECM) imaging of tissues. The spider array contains up to eight completely individual, parallel, and flexible carbon microelectrodes designed to scan square centimeter sized areas on reasonable time scales while avoiding sample aging and electrode fouling. The contact mode enables the scanning of largely curved samples at a constant distance. The spider array is applied for the SECM imaging of the distribution of certain biomarkers, such as tyrosinase, in thin tumor tissues as well as thick tumor blocks. Furthermore, the spider array can be applied for mapping the antioxidant distribution in an apple peel.